Diastolic Blood Pressure as a Predictor of Mortality in Intracerebral Hemorrhage Stroke Patients with Hypertension - Cep Juli; Uni Gamayani; Nur Atik (Althea Medical Journal, 2021)
Background: Intracerebral hemorrhage (ICH) stroke contributes to a considerable number of deaths, ranging between 30% and 40% of the overall stroke mortality. The incidence of stroke increases with higher blood pressure. High blood pressure at the onset of ICH stroke is a strong predictor for mortality and morbidity. This study aimed to explore the role of diastolic blood pressure as a predictor of death in ICH stroke patients.Methods: Data on 113 ICH stroke patients with chronic hypertension were collected from the medical records of patients treated in the Neurology ward of Dr. Hasan Sadikin General Hospital Bandung, Indonesia, in 2019. Data collected were patient characteristics, hypertension status, systolic and diastolic blood pressures, and patient outcome. Analysis was then performed using the Mann-Whitney test.Results: This study revealed a positive correlation (p=0.031) between diastolic blood pressure and death in ICH stroke patients with chronic hypertension.Conclusion: High diastolic blood pressure is associated with mortality in ICH stroke patients with chronic hypertension.